PENGARUH KUALITAS PELAYANAN TERHADAP MINAT KUNJUNGAN ULANG PELANGGAN PADA LAYANAN REFLEKSI DI KAMARI WELLNESS REFLEXOLOGY KOTA PADANG - Ilfa Anggina; Murni Astuti (Ensiklopedia of Journal, 2026)
Abstract: This study aims to analyse the quality of SPA services, examine customers' interest in revisiting, and analyse the effect of SPA service quality on customers' interest in revisiting at Kamari Wellness Reflexology. The research used is quantitative research with a causal associative approach. The population and sample of this study were all customers of Kamari Wellness Reflexology who revisited the reflexology service at least twice during the two-month period of August and September, totaling 124 people. Data were collected through interviews and questionnaires. The data were analysed using prerequisite analysis tests and hypothesis testing. The results showed that the better the service quality provided by Kamari Wellness Reflexology Padang City, the higher the customers' interest in revisiting. The service quality at Kamari Wellness Reflexology in Padang City is classified as good, with an average respondent response score of 4.32 and a Respondent Achievement Level (TCR) of 86.4%. Customer repurchase interest at Kamari Wellness Reflexology is also in the  good category, with an average score of 4.31 and a TCR of 86.2%, indicating that customers have a strong desire to return for reflexology services. Service quality has a positive and significant effect on customer repurchase interest, with a simple linear regression test showing a t-value of 14.402 and a significance (Sig.) of 0.000 0.05, which means that an improvement in service quality can significantly increase customer repurchase interest. The determination coefficient (R²) value of 0.554 indicates that 55.4% of the variation in repeat visit interest can be explained by the Service Quality variable, while the remaining 44.6% is influenced by other factors such as price, location, promotion, and the customer's personal experience.Keywords: Quality, Service, Repeat Visits, Customers.